Exploring the Impact of Artificial Intelligence on Enterprise Modeling - Denis Denunciar Otros; Vistos Otras (International Journal of Enterprise Modelling, 2019)
This research investigates the impact of artificial intelligence (AI) on enterprise modeling, with a specific focus on supply chain network design. The objective is to explore how AI techniques can enhance decision-making, improve efficiency, and drive cost reduction in enterprise modeling processes. The research utilizes case examples and numerical simulations to demonstrate the benefits and implications of incorporating AI techniques in enterprise modeling. The findings reveal that AI-enabled approaches in supply chain network design lead to cost reduction, improved customer service levels, accuracy improvement, efficiency gains, enhanced decision-making, and collaboration facilitation. The research highlights the importance of data availability, ethical considerations, organizational readiness, and interoperability in realizing the full potential of AI-enabled enterprise modeling. However, the research acknowledges the limitations, such as simplified examples and the specific context of supply chain network design. Future research is needed to validate the findings in diverse industry settings and address challenges related to data availability, ethical considerations, organizational readiness, and interoperability. This research contributes to the understanding of the positive impact of AI on enterprise modeling, providing valuable insights for organizations seeking to leverage AI techniques to optimize their decision-making processes and drive operational improvements.